Answer:
Explanation:
Step 1: Subtract 8cx from both sides of the equation to get
10ax + 9b - 8cx = d
Step 2: Subtract 9b from both sides of the equation to get
10ax - 8cx = d - 9b
Step 3: Multiply both sides of the equation by (-1/10) to get
-8cx/10 = -(d - 9b)/10
Step 4: Add (d - 9b)/10 to both sides of the equation to get
-8cx/10 + (d - 9b)/10 = 0
Step 5: Simplify the left side of the equation to get
x = (9b - d)/80
Therefore, x = (9b - d)/80 is the solution to the equation 10ax + 9b = 8cx + d.